Thrombin and plasmin activity in coronary artery disease. Issue 3 (September 1988) - Small, M; Lowe, G D; Douglas, J T; Hutton, I; Lorimer, A R; Forbes, C D
Abstract : Basal plasmin and thrombin activity in plasma were assessed by radioimmunoassay of the fibrinogen derivatives containing the sequence B beta 15-42 and of fibrinopeptide A respectively in a cross sectional controlled study of men with coronary artery disease. Compared with healthy controls (n = 33) men with angiographically defined coronary artery disease (n = 98) had a modest but significant increase in concentrations of fibrinopeptide A, indicating an activated coagulation system. Concentrations of B beta 15-42 were similar in those with coronary artery disease and in the controls. The enhanced thrombin activity in coronary artery disease is in keeping with current evidence suggesting an association between coronary artery disease and a hypercoagulable state.